(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2020)
The ichnology of the Pleistocene sand sequence of Gravina is described. The trace fossils provide evidence for marine coastal environments, ranging from the lower infralittoral to intertidal. The study is based on two sections, at Lama La Noce and at Notargiacomo’s Quarry respectively. Meniscate backfill structures produced by echinoids (Schizaster canaliferus) occur in thin clay horizons. Sand subst-rates are dominated by Ophiomorpha, Thalassinoides, Cylindrichnus and vertical equilibrium traces. Two new ichnospecies are erected: Cylindrichnus errans, which has lateral spreite—like displacement of the shaft: and Dactyloidites peniculus for finely branched, radiating spreite structures.